EXPLORING AUTONOMOUS AND SELF-REGULATION IN VOCABULARY LEARNING - Thania Imani Janitra; Mutmainnah Mustofa; Imam Wahyudi Karimullah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Vocabulary is the most fundamental aspect of language learning. However, the limitation of classroom-based vocabulary learning to cover large amount of vocabulary, implies the necessity of learning vocabulary independently and regulate their learning effectively. This study aims to identify the learners’ autonomy and self-regulation strategies in learning vocabulary as well as the benefits and difficulties of independent vocabulary learning. This study implements descriptive qualitative design with questionnaire as instrument in data collection. The researcher collects the data taken from 10 late-semester students in University of Islam Malang. The result shows that all students learn vocabulary independently on their own preferences, but only four students are autonomously self-regulate, the other respondents considered ineffective in self-regulation. In the identification of independent learning benefits and difficulties, the researcher found seven benefits and five problems. The research concludes that 10 out of 21 students are independent learners, but only 4 out of 10 students considered as an effective autonomous learners. Independent learners is greatly benefits vocabulary learning. Meanwhile most of the problems encountered by the students in this study aside from difficult words signify similar difficulties of other independent learning.Key Words: Autonomous, Independent-learning, self-regulated vocabulary learning